The virtual executive [ how to act like a CEO online and offline - Benton, D. A. [ (Debra A.)] (New York : McGraw-Hill, 2012)
Teaches you about the things you need to know to navigate seemingly endless choices of social media and virtual communication tools in order to stay relevant in a sea of competition. From videoconferencing, instant messaging, and webinars to LinkedIn, Facebook, and Twitter, this title explains how and when to use each platform
1. Voice channel -- 2. Video channel -- 3. Written channels -- 4. Online communities channels -- 5. Users' stories
Includes index
Keywords: Communication in management; Executive ability; Executives